2019
DOI: 10.21142/2523-2754-0602-2018-158-166
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia de dientes supernumerarios en niños de 6 a 12 años en la ciudad de Huánuco del 2012 al 2016

Abstract: Objetivo: Determinar la prevalencia de dientes supernumerarios identificados mediante radiografías panorámicas enniños de 6 a 12 años de la ciudad de Huánuco, durante el período 2012-2016. Materiales y métodos: La muestra fuede 523 radiografías panorámicas de pacientes entre 6 y 12 años. Se realizó la observación detallada de cada radiografíapanorámica por sextantes verificando cada una de las piezas dentarias y gérmenes dentarios adyacentes. Se usó una ficha para el registro de la información donde se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Still, the results showed that the prevalence varied between the Peruvian, Bolivian, and Colombian populations; these results could be explained by racial diversity, in the Peruvian and Bolivian population their descendants are indigenous in 45% and 55% respectively, while in Colombia their population is mestizo in a greater proportion (49.9%). [19] These results should continue to be corroborated within other cities in the same countries to see if the trend remains or shows variations from those reported, however, this prevalence remains low. From the results of the present work and the analysis of the bibliography studied, it is highlighted that mesiodens is the dental anomaly with the highest presence, with panoramic radiography being an important diagnostic tool for its determination and easily accessible.…”
Section: Discussionmentioning
confidence: 66%
“…Still, the results showed that the prevalence varied between the Peruvian, Bolivian, and Colombian populations; these results could be explained by racial diversity, in the Peruvian and Bolivian population their descendants are indigenous in 45% and 55% respectively, while in Colombia their population is mestizo in a greater proportion (49.9%). [19] These results should continue to be corroborated within other cities in the same countries to see if the trend remains or shows variations from those reported, however, this prevalence remains low. From the results of the present work and the analysis of the bibliography studied, it is highlighted that mesiodens is the dental anomaly with the highest presence, with panoramic radiography being an important diagnostic tool for its determination and easily accessible.…”
Section: Discussionmentioning
confidence: 66%
“…In 2018, Zevallos et al [19] analyzed 523 panoramic views of patients between 6 and 12 years old of both sexes who attended a radiographic center in the city of Huanuco (Peru); 67 patients with ST were found. Of the 67 patients, 39 were men (52.23%) and 33 women (47.76%).…”
Section: Discussionmentioning
confidence: 99%